Debt dynamics and contingency financing: Theoretical reappraisal of the HIPC initiative - Machiko Nissanke; Benno Ferrarini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
The objective of this paper is to examine debt dynamics of highly indebted poor countries (HIPCs) and identify key factors responsible for their protracted debt crisis. For this purpose, we first evaluate economic conditions of debt sustainability in the context of the intertemporal borrowing model, the growth-cum-debt model and the gap models. After reviewing other concepts of debt dynamics, such as liquidity problem and insolvency condition, we analyse mechanisms whereby a debt burden becomes unsustainable and debt forgiveness is a rationale choice for both creditors and debtors to overcome the ensued debt overhang condition. In the light of these theoretical expositions, we present empirical evidence as to how debt dynamics has evolved over the last two decades in selected HIPCs and question the effectiveness of ex post debt relief facilities applied so far. In the concluding section, we present our proposal to use a state-contingent debt contract as an ex ante debt relief mechanism, as opposed to the current ex post debt relief embedded in the HIPC initiative, which we view as an ineffective mechanism for debt-crisis prevention and management.
Keywords: F34; F35; O11; O19; 330; sovereign debt management; external debt; foreign aid; growth models; economic development; Auslandsverschuldung; Debt Management; Entwicklungsländer